Strategic Air Command [videorecording (DVD)] - Stewart, James, 1908-1997; Allyson, June, 1917-2006; Lovejoy, Frank, 1912-1962 (Olive Films, 2016)
Set in the 1950s, a successful player for the St. Louis Cardinals baseball team attempts to balance domestic life, and service to God and country, after suddenly becoming active for the U.S Air Force and being promoted to commanding a bomber crew.